FACTORS AFFECTING ACCOUNTING CONSERVATISM FOR FOOD AND BEVERAGE SUB SECTOR BETWEEN 2016-2020 PERIOD - Novi Nugrahani; Fita Setiati; Siti Amerieska (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2021)
It is challenging that food and beverage sub-sector is growing rapidly these days. As a matter of fact, there are various variables affecting the accounting conservatism in food and beverage industry. The purpose of this study is to determine simultaneously and partially the factors that influence accounting conservatism. These factors are debt covenant, company growth, financial distress, litigation risk, and political costs. The population of this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study applied purposive sampling technique in selecting the sample of this study. This study used multiple regression analysis using SPSS software. The partial test showed that debt covenant and financial distress had a significant effect on accounting conservatism. Besides, the variables of company growth, financial distress, and political costs had no significant effect on accounting conservatism. Simultaneous test results showed that there was a significant influence of debt covenant, company growth, financial distress, litigation risk, and political costs on accounting conservatism. Further research is encouraged to be conducted on companies listed on IDX from various sub-sectors other than food and beverage to broaden the coverage. Also, it would be interesting to observe other factors affecting accounting conservatism through other periods to compare the results.Keywords: accounting conservatism, food and beverage sub-sector, 2016-2020 period